UTILIZATION OF DATA-BASED HUMAN RESOURCE MANAGEMENT APPLICATIONS IN IMPROVING EMPLOYEE PERFORMANCE AT CV MEKAR JAYA GROUP - M. Fulviano Cahya Hadi Kusuma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
CV Mekar Jaya Group is a company engaged in the distribution of several products, such as Bottled Drinking Water (AMDK), Cigarettes, Household Goods, and others. In addition to having various warehouses that store product distribution, CV Mekar Jaya Group also has a main office called the Head Office. From there, all employees consisting of various positions carry out their duties. In the Head Office, CV Mekar Jaya Group takes advantage of the era of globalization which has caused technology to develop rapidly, to use data-based applications in daily activities. One of them is the Human Resource Management Application. CV Mekar Jaya Group uses the Human Resource Management Application as a means for quick access to employees. In its use, the Human Resource Application provides complete and accurate features and information regarding all employees working in all branches of CV Mekar Jaya Group. This journal aims to provide information to business actors, especially startup businesses in managing data-based employees and finding prospective employees who are suitable for the company's vision and mission. And from CV Mekar Jaya Group we will also learn how important the Human Resource Management Application is very effective in managing employee performance, recruitment of prospective employees, and employee discipline. The results of this study show that data analysis can identify employee capabilities, gradual employee growth, and employee performance reviews. The analysis strategy will be able to improve employee performance, and of course from the management in its ease of managing employees and decision making in the future.